2012
DOI: 10.1149/2.005303eel
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectrochemical Poperties of Anodic TiO2 Nanosponge Layers

Abstract: In the present work we grow TiO 2 nanosponge structures by anodizing Ti in a glycerol/water/NH 4 F electrolyte to thickness of some m. We evaluate the photoelectrochemical behavior (band gap, photocurrent-voltage characteristics) in presence and absence of methanol. Methanol drastically affects the photoresponse (due to hole capture and current doubling). The optimum thickness for photoelectrochemical applications of these nanostructures is dependent on the excitation wavelength. For applications such as sola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…In the latter case, several nanostructured TiO2 networks (e.g. tubes [15][16][17], rods [18][19][20], wires [21,22], sponges [23,24]) emerged as promising materials that can be used as photoanodes in water photoelectrolysis cells. In particular, as summarized in very recent reviews [25][26][27][28][29][30], extensive research has been performed on TiO2 nanotube arrays (T-NTs) because their unique high surface-to-volume ratios (even though not as high as those obtained with nanoparticle assemblies), ordered geometry and tunable morphologies are claimed for fast charge separation and transport, and 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 electrolytes in the case of photoelectrochemical solar cells, pollutants or reagents in the case of photocatalysis), and also (iv) anisotropic morphology (similarly to nanotubes or nanowires) to ensure better electron transport towards the electrical contact [31,32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the latter case, several nanostructured TiO2 networks (e.g. tubes [15][16][17], rods [18][19][20], wires [21,22], sponges [23,24]) emerged as promising materials that can be used as photoanodes in water photoelectrolysis cells. In particular, as summarized in very recent reviews [25][26][27][28][29][30], extensive research has been performed on TiO2 nanotube arrays (T-NTs) because their unique high surface-to-volume ratios (even though not as high as those obtained with nanoparticle assemblies), ordered geometry and tunable morphologies are claimed for fast charge separation and transport, and 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 electrolytes in the case of photoelectrochemical solar cells, pollutants or reagents in the case of photocatalysis), and also (iv) anisotropic morphology (similarly to nanotubes or nanowires) to ensure better electron transport towards the electrical contact [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…In the latter case, several nanostructured TiO2 networks (e.g. tubes [15][16][17], rods [18][19][20], wires [21,22], sponges 23 [23,24]) emerged as promising materials that can be used as photoanodes in water photoelectrolysis cells. In particular,…”
mentioning
confidence: 99%
“…The latter has the advantage of removing the "initiation layer" in the same process of anodization and, therefore, other independent processes in order to remove this layer are not needed. Moreover, the use of hydrodynamic conditions can significantly affect on the final TiO 2 nanotube geometry [22,26,27]. After anodization, an amorphous structure is obtained which implies the presence of a high number of defects.…”
Section: Introductionmentioning
confidence: 99%
“…Anodization of titanium in fluoride-based electrolytes is other possible method, in fact it is one of the most promising method to synthesize TiO2 nanotubes because it allows obtaining highly ordered nanotube arrays directly grown into the Ti substrate, and their dimensions (length, diameter, and tube wall) can be precisely controlled [40][41][42]. In previous works, the authors showed that under specific anodization in glycerol/water electrolytes and using hydrodynamic conditions, a transition from a TiO2 nanotube morphology (stagnant conditions) to a nanosponge morphology (hydrodynamic conditions) occurs [34,43,44]. These nanosponges provide better performance for water splitting than the tube morphologies obtained in glycerol/water electrolytes [34].…”
Section: Introductionmentioning
confidence: 99%
“…As an example,Figure 3shows the top surface of the nanostructure formed at Re=600. This nanostructure is called nanosponge and is characterized by a connected and highly porous TiO2 structure[34,43,44].…”
mentioning
confidence: 99%